Finally, the chance to eat healthily: Longitudinal study about food consumption during and after the first COVID-19 lockdown in Italy. (January 2022) - Caso, Daniela; Guidetti, Margherita; Capasso, Miriam; Cavazza, Nicoletta
Highlights: During lockdown, perceived healthy food intake and involvement in cooking increased. Perceived junk food consumption decreased during lockdown. After lockdown, healthy food consumption and involvement decreased. Junk food intake kept declining even after lockdown. Restrained eaters' consumption patterns took the greatest advantage of the lockdown. Abstract: With the COVID-19 outbreak, structural constraints and social psychological factors changed the dietary habits of many people. This two-wave longitudinal study performed in Italy aimed to explore people's perceptions of changes in healthy and unhealthy food consumption before and during the first lockdown and the possible persistence of such changes after its official end, as a function of the number of people cohabiting, negative emotion activation, and individual eating styles. A total of 728 Italian adults completed self-reported food consumption measures and related psychological variables at both time points. In the lockdown period, participants reported an increase in healthy food consumption and involvement in cooking and a decrease in the consumption of junk food. This general pattern was stronger for both young and restrained eaters. The intensity of negative emotions and the number of cohabitants were not associated with the examined behaviour. In the post-lockdown period, the new consumption pattern acquired during the confinement was partially discontinued: participants cut down their healthy food consumption as well as their involvement in food preparation, but they continued to reduce their junk food intake. These results suggest that people's food consumption patterns can easily improve when the situation is favourable (e.g., more time and opportunities for cooking healthy meals) and offer an interesting theoretical contribution to understanding the factors useful in promoting healthy eating, in the event of a future outbreak.